The Challenges of Teaching for English Specific Purposes in Higher Education - septiana, ira (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2018)
English for Specific Purposes appeared due to the awareness that general English course was not suitable for the learners? need, especially in higher education. In teaching  ESP, the materials are focused on the learners? needs or their specific fields of study and it is assumed that they have basic language skills of general English. The purpose of this study was to analyze the challenges that arise in teaching English for Specific Purpose (ESP) in higher education. This article is aimed at describing some of the learning problems esp. A lot of the problems  from the teachers, materials production, the error of learner assessment. In order to minimize these effects, some solutions are offered. The solutions are increase the ability of lecturers ,materials development, and the course evalution.